The value of increasing sequencing depth for noninvasive prenatal screening for whole chromosomal aneuploidy - Dongmei Wang; Fangfang Guo; Yaping Hou; Haishan Peng; Tingting Hu; Jiexia Yang (Scientific Reports)
Abstract To evaluate the value of increasing sequencing depths of non-invasive prenatal testing (NIPT) for fetal chromosomal aneuploidies based on the semiconductor sequencing platform. This study recruited a cohort of 59,800 singleton pregnancies from Guangdong Women and Children Hospital between January 2015 and December 2020, including 48,018 cases of NIPT and 11,782 cases of expanded NIPT. Cell-free DNA from plasma samples was sequenced at a sequencing depth of 0.15X for NIPT and 0.4X for expanded NIPT. Patients with positive NIPT results were offered fetal karyotyping or microarray analysis for confirmatory testing, and all pregnant women were followed up. A total of 892 cases were predicted as positive for chromosomal aneuploidies, including 682 cases of NIPT and 210 cases of expanded NIPT, with a positive rate of 1.42% and 1.78% (p = 0.0037), respectively. The positive predictive values (PPV) for trisomy 21/18/13 and other autosomal aneuploidies detected by NIPT were 84.80%, 69.23%, 25.00%, and 4.55%, respectively. For expanded NIPT, the positive predictive rates were 86.96%, 80.00%, 35.00%, and 8.77%, respectively. Both NIPT and expanded NIPT have the same PPV for detecting sex chromosome aneuploidies (approximately 50%). Additionally, one false-negative case was identified during the follow-up period. This was a trisomy 18 confirmed by prenatal diagnosis due to multiple ultrasound abnormalities during pregnancy. The study shows that increasing sequencing depth can significantly improve the PPV performance of aneuploidies, with a statistically significant difference, particularly in trisomy 18. The results may provide valuable guidance for clinical doctors during consultations.